Three-step Interview Technique to Improve Students’ English Speaking Skill - Hidayat, Ade; Ariani, Desti (LPPM Politeknik Raflesia, 2023)
This study aims to investigate the implementation of Three-step interview technique in improving students’ English-speaking skill. Designed as classroom action research with 31 college students for the research subjects, through pre-test, post-test, observation checklist, and interview, it is found that Three-step interview technique have positive effect and can improve students’ English-speaking skill. Majority of the students show improvement in their speaking skill and indicate that the implementation of Three-step interview technique has made the learning activities become more fun, challenging, and make them become more enthusiastic during the learning. Besides, there are also indications that this technique improves students’ motivations and attitude towards learning English.